Innovative Reconstruction Techniques for Extensive Head and Neck Tumors - Bezerra Toscano Mendonça, Ullyanov; Correia Lima, Bernardo; Grillo, Ricardo; Peral Ferreira Pinto, Leonardo Augustus (European Journal of Therapeutics, 2024)
In the challenging landscape of malignant head and neck tumors, surgeons grapple with intricate obstacles to achieve effective reconstruction. When facing extensive involvement of soft and bone tissue, reestablishing acceptable aesthetics and function to patients should always be focused on restoring both form and function, we encountered a compelling case—a significant squamous cell carcinoma deeply rooted in the anterior mandibular region, necessitating substantial soft tissue and bone resection. Our innovative approach involved a carefully tailored extended prosthesis designed for the mandible and its temporomandibular joint, accompanied by a skillfully deployed deltopectoral myocutaneous flap. This surgical intervention successfully brought about the triumphant resurgence of reconstruction of mandibular function, marking a state of disease-free well-being for the patient. This narrative unfolds at the forefront of transformative reconstruction, where the synergy of innovation and expertise redefines the narrative, showcasing victory over adversity in the intricate realm of head and neck tumor surgery.